THE STUDY CRITICALLY EXAMINES THE LAW OF SEDITION IN INDIA AND EXPLORES THE SUPREME COURT'S INTERVENTION IN SPECIFIC CASES, WITH A FOCUS ON THE RECENT INSTANCE INVOLVING A SHOPKEEPER IN UTTAR PRADESH - Uddin, Rafiq; Yadav, Mithilesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study critically examines the law of sedition in India and explores the Supreme Court's intervention in specific cases, with a focus on the recent instance involving a shopkeeper in Uttar Pradesh. Section 124A of the Indian Penal Code (IPC) defines and criminalizes sedition, but its broad interpretation and potential for misuse have raised significant legal and ethical concerns. The Supreme Court of India has played a pivotal role in interpreting and limiting the scope of this law to prevent abuse and protect fundamental rights. Through a detailed analysis of judicial precedents and recent cases, this study aims to highlight the ongoing challenges and implications of sedition law in India.